Comparative evaluation of two autotransfusion devices in a 72h survival swine model of surgically induced controlled splenic bleeding - Axelle Castelli; Chloé Libaud; Benoît Decouture; Marine Bruneau; Mallorie Depond; Patricia Forest-Villegas; Olivier Gauthier; Audrey Lafragette; Gwenola Touzot-Jourde (PLoS ONE, 2025)
Autotransfusion is a key strategy in hemorrhagic surgical procedures, reducing risks like disease transmission and immunosuppression due to allogenic transfusion. While conventional devices efficiently process red blood cells by centrifugation, they don’t address complications requiring additional platelet transfusions. The innovative same™ device (i-SEP, France), utilizing hollow-fiber filtration, preserves both red blood cells and platelets without damaging cell integrity. This study designed as a prospective randomized controlled trial compared cell concentration and washout performances of two autotransfusion devices, a preclinical version of same™, the conventional centrifugation-based Xtra® (LivaNova, UK); and effects of retransfusion versus no transfusion in 21 Yucatan minipigs submitted to a surgically induced controlled splenic bleeding. Animals were divided into three groups (no-transfusion control group, same group and xtra group) and monitored postoperatively for 72 hours during which serial animal blood samples were collected for hematologic, biochemical and coagulation analyses and tests. Both autotransfusion devices showed high performances in red blood cell yields and concentrations, with a significant superiority of same™ device to preserve platelets. Animals from same and xtra groups retrieved similar rheological profiles and maintained a normal hematocrit compared to no-transfusion control animals. Coagulation profiles stayed within normal range in all groups. No adverse event on animals nor post-mortem sign of thrombosis were identified on autotransfused animals. The same™ device that can therefore be considered as an interesting alternative to conventional centrifugation-based devices. Further experiments are needed to provide evidence of platelets autotransfusion benefits in massive hemorrhagic procedures.